2004
DOI: 10.1097/01.phm.0000143400.15346.c8
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine in Pediatric Patients with Traumatic Brain Injury

Abstract: Amantadine is a well tolerated medication when it is used in pediatric patients with traumatic brain injury. Subjective improvements were noted in the majority of the patients administered amantadine, and the amantadine group showed a greater improvement in Ranchos Los Amigos level during admission, suggesting that it may be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…12 A retrospective, case-controlled study examined changes in recovery in children with TBI who either received amantadine or did not receive neurostimulants. 13 Amantadine administration was associated with a lower initial Ranchos Los Amigos level, but the group that received amantadine did not have a longer length of posttraumatic amnesia or length of stay, suggesting that amantadine may have a beneficial effect. Another retrospective review evaluated children with impaired arousal after a TBI who received various dopaminergic medications, by comparing responsiveness during periods before and after initiation of medication.…”
mentioning
confidence: 94%
“…12 A retrospective, case-controlled study examined changes in recovery in children with TBI who either received amantadine or did not receive neurostimulants. 13 Amantadine administration was associated with a lower initial Ranchos Los Amigos level, but the group that received amantadine did not have a longer length of posttraumatic amnesia or length of stay, suggesting that amantadine may have a beneficial effect. Another retrospective review evaluated children with impaired arousal after a TBI who received various dopaminergic medications, by comparing responsiveness during periods before and after initiation of medication.…”
mentioning
confidence: 94%
“…In 2004, a retrospective case–controlled study evaluated the use of amantadine in 54 children, ages 3–18 years. Outcomes included change in Rancho Los Amigos Score (Rancho score), length of post-traumatic amnesia, and length of hospital stay [21]. Amantadine use at a dose of 400 mg was well tolerated in the majority of participants.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…23,73,74 In a retrospective, case-controlled study of 54 pediatric patients, Green and colleagues 73 concluded that amantadine was safe and well-tolerated after traumatic brain injury and lead to subjective improvement as well as significant increases in Ranchos Los Amigos scores. Similarly, Beers and colleagues 74 studied the effects of amantadine in pediatric patients after traumatic brain injury and concluded that the medication was safe in this setting.…”
Section: Cognitivementioning
confidence: 99%